Forage Fact Sheet Tithonia - Eje Transversal Innovación y Tecnología (ETIT) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
Brief explanation of the Tithonia: plant description, forage management, cultivation, cutting, transplanting, fertilization and use